(3WHbGJ GdabgGA hGdeMOKjf GdeJhajf SfI (B612(3g`s - (3GdTjN eMji GdOjfs
(3ChdgG (B:s
(3SfI GKfJi YTQI hSJeGFI ai ChGFd GdeMQe JhajJ MaUI HfJ CMeO Hf eMeO GHf edGYH GdHZOGOjI s
(3BNQgG (B:s
(3hai gPg GdSfI Jhaj GdTjN CHhGdMSf Ydi Hf CMeO Hf Ydi Hf HWhTG, MOK Yf GdMGaX CHj GdaVd eMeO Hf fGUQ, QVhGf Gddg Ydjge CLeYjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B221 - (3U(B227s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B278 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY (B125) s
Keywords: (3GdJGQjNs